Extraction and quantitation of total peptides and proteins from the whole plant Crotalaria pallida and determination of antimicrobial activity of the isolated peptides and proteins - Sikta, Shishir Ahmed (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.